2020
DOI: 10.1021/acs.langmuir.0c00382
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Au@Cu2O Core–Shell Nanoparticles with Tunable Shell Thickness and Their Degradation Mechanism in Aqueous Solutions

Abstract: Metal@semiconductor core−shell nanoparticles (NPs) are widely used in photocatalysts, sensors, and optical applications owing to their unique metal−semiconductor interface and the integration of the properties from both core and shell materials. Although many efforts have been made toward the precise synthesis of Au@Cu 2 O core−shell structures, the chemical stability of Au@Cu 2 O aqueous suspensions, which is of great significance in many related applications, is not mentioned in any published research. Herei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 31 publications
1
23
1
Order By: Relevance
“…1b). Compared with the absorption peak of Cu 2 O nanocrystals, the absorption peak of Au@Cu 2 O NCs is blueshifted and broadened due to the interband transition and scattering of the Cu 2 O shells 31 . When Ag nanocrystals were immobilized on Au@Cu 2 O NC shells, the absorption bands shifted further to lower wavelengths due to the interaction between Au@Cu 2 O NCs and Ag nanocrystals 32 .…”
mentioning
confidence: 95%
“…1b). Compared with the absorption peak of Cu 2 O nanocrystals, the absorption peak of Au@Cu 2 O NCs is blueshifted and broadened due to the interband transition and scattering of the Cu 2 O shells 31 . When Ag nanocrystals were immobilized on Au@Cu 2 O NC shells, the absorption bands shifted further to lower wavelengths due to the interaction between Au@Cu 2 O NCs and Ag nanocrystals 32 .…”
mentioning
confidence: 95%
“…Additionally, the degree of induced excitation CT process at the metal–semiconductor interface depends on the parameter and dielectric properties of the semiconductor. For example, the UV-vis absorption properties and the chemical stability of Au@Cu 2 O core−shell nanoparticles are found to be tunable with Cu 2 O thickness [ 24 ]. Zhao et al [ 25 ] found that the CT degree of the Ag/PATP/ZnO system depends on the size of ZnO nanoparticles, and the possible CT resonance mechanism was responsible for the size-dependent SERS behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The study of SPR and interfacial CT process provides vital information on the interfacial interaction of substrate materials and also provides a theoretical basis for the optimal design of excellent SERS substrates. At present, the effect of the semiconductor thickness on the SERS and photocatalytic performance in hybrid systems has been reported [ 24 , 28 , 29 , 30 ]. However, the SPR and CT mechanism, as well as the CT process at the substrate–molecule interface related to semiconductor thickness changes, are rarely studied in the composite system.…”
Section: Introductionmentioning
confidence: 99%
“…Among the potential hybrid nanostructures, the metal@semiconductor core-shell heterostructure has been extensively studied because this composite material combines two completely different materials together to form a unique structure with synergistic properties and functions [16,17]. Among these materials, the Au NP@semiconductor structure is widely used in photocatalysis, solar cells, biology, sensing, and other fields [18][19][20][21][22]. Compared with Au NPs, Au nanorods (NRs) are also a commonly used SERS substrate.…”
Section: Introductionmentioning
confidence: 99%